Assessment of citrus rootstocks against dry root rot induced by Fusarium solani - Parshuramkar, L Y; Ingle, Y V; Chandurkar, R S; Shinde, V P; Avantika, M B (Plant Science Today, 2026)
Citrus rootstocks play a vital role in imparting tolerance or resistance to diseases. Dry root rot induced by Fusarium solani is one of most destructive soil-borne diseases of citrus. The present study was conducted under the All India Coordinated Research Project (AICRP) on Fruits scheme at Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola, to evaluate the tolerance of different citrus rootstocks against F. solani. A total of 8 rootstocks (NRCC-1, NRCC-2, NRCC-3, NRCC-4, CRH-12, Rangpur lime, Alemow and Jambheri) were evaluated using different screening methods, including the seedling inoculation method, leaf inoculation with injury, leaf inoculation without injury and application of culture filtrate on wounded leaf segments. All the examined rootstocks exhibited variable levels of susceptibility to dry root rot. In the seedling inoculation method, rootstock mortality ranged from 20.00 % in Rangpur lime to 60.67 % in Jambheri. Leaf lesion lengths following injury ranged from 14.45 mm (Rangpur lime) to 24.43 mm (Jambheri), whereas without injury lesions ranged from 11.95 mm (Rangpur lime) to 20.43 mm (NRCC-4). Culture filtrate bioassays produced lesion areas ranging from 1.01 cm² (Rangpur lime) to 1.69 cm² (NRCC-1). Among the evaluated rootstocks, Rangpur lime exhibited comparatively higher tolerance to F. solani. Leaf inoculation with injury was found to be a rapid and reliable method for screening citrus rootstocks against dry root rot.